An Analysis of Teaching Methods and Techniques of Learning Economics in Nigeria - Mugu, Juliana Yusuf; Tope, Eniwaiye (NIU Journal of Humanities, 2018)
Teaching and learning can be accomplished and sustained if teachers can manage classroom effectively; subject matters are properly dealt with and comprehensible teaching methods and techniques are used. The significant of methods and techniques in the teaching and learning process cannot be overemphasized because it has become crescent clear that methods and techniques used in teaching/learning Economics. These methods include lecture method, problem-solving method and question method among. The paper consider factors to be consider before chosen any of methods; and when questions are to be ask when using the questioning method. For purpose of discussion methods, there are fundaments that teachers must know before using such method. Recommendations are also given in this paper, that teachers must have a look at the subject matter to be taught before chosen a particular method. Student’s ability to think critically and their ability to perform independent inquiry must be considered. Lastly, method use by the teacher must covered the three domains; cognitive, affective and psychomotor.